Process Bases for Ensuring Interoperability and Synchronization of Multifunctional Network-Centric Systems - Kozlov, S. V.; Kubankov, A. N. (Systems of Signal Synchronization, Generating and Processing in Telecommunications (Online), 2024)
The article discusses the process aspects of the complex problem of interoperability in the creation and operation of automated control systems as multifunctional integrated systems based on network-centric principles. It is noted that the integration of functional systems vertically (in terms of including several levels of the management hierarchy) and horizontally of interaction (in terms of expanding the variety of combined functional systems), as their complexity increases, leads to a rapid increase in the dimension of the network-centric system, which, in turn, expands the subject area of the problem of interoperability of its constituent functional systems and at the same time increases the complexity of the analysis of its problem area. On the other hand, in the field of general management, there is a tendency to move from automation of functional tasks to automation of management processes that combine the performance of several interrelated tasks, and, ultimately, to automation of organizational processes (business processes). It is noted that the need to apply a process approach to the development of network-centric systems as integrated multifunctional systems is determined, on the one hand, by the complexity of the traditional functional approach to ensuring the interconnected implementation of an increasing number of management tasks using network-centric systems as a qualitatively new high-tech infocommunication basis and, on the other hand, the actual transition from automation of (most often disconnected) management tasks to automation of business processes. The necessity of clarifying the composition of the process system in the life cycle of network-centric systems with the allocation of complete groups of target functional processes and supporting processes of system engineering is shown. The ontology of the subject and problem areas of the network-centric system as an integrated management system is presented and an integrated approach to the application of a process approach to their analysis is explained.